Business Opportunity : Matang Dagang Enterprise / Ahm Muhaimi Mohd Arrfin - Mohd Arrfin, Ahm Muhaimi (2021)
The overview of this report is I am proposing the business that I choose which is MATANG DAGANG Enterprise through the process that showed in Business Model Canvas. MATANG DAGANG Enterprise is the one I choose for this report. MATANG DAGANG Enterprise is akampong Matang based company that supply animal feed. This report was paid particular attention more to the customer, value proposition, channel, customer relationships, revenue stream, key activities, key resources, key partners and cost structure of the company and make recommendations or some innovations that would improve MATANG DAGANG Enterprise current performance.